An Analysis of EFL Students Perspective on Classroom Activities during Extensive Reading Class - Panggabean, Christina Innocenti Tumiar; Triassanti, Risa; Avila Kurniawati, Sintia; Ambarsari, Lusi; Novitasari, Dwi (Journal of Education, Language Innovation, and Applied Linguistics, 2023)
This article aims at explaining the EFL students’ perspectives on classroom activities on classroom activities during Extensive Reading Classes. To be specific it describes the classroom activities and the students’ perspectives on the activities in Extensive Reading Classes. Descriptive qualitative is used as the research design of this study. The participants of this study were a lecturer of the Extensive Reading class and 12 students of the English language education class 2019 in the Faculty of Teacher Training and Education of PGRI Ronggolawe University. To collect the data observation using video recording, questionnaire, and interview were used. The data were analyzed descriptively. From the analysis, the result showed that classroom activities used in Extensive Reading classes were reading activities by individual students in which the students chose their reading materials freely, and then they chose two reading materials to be presented in the class. From the study, it was also found that the students felt satisfied with the activities and stated that they could improve their reading skills after taking the Extensive Reading Class. However, the students agreed that the classroom needed some improvement to make the activities more fun and interactive. Keywords: Classroom Activities; Extensive Reading; Students Perspective; Qualitative.